1982
DOI: 10.1111/j.1398-9995.1982.tb04114.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective Serotonin (5‐HT) Transport Mechanism in Platelets from Patients with Endogenous and Allergic Asthma

Abstract: The kinetics of the 5-HT-uptake by platelets in platelet-rich plasma (PRP) and PRP diluted with autologous platelet-poor plasma (PRP/PPP) were determined in normal subjects, patients with asymptomatic exogenous asthma and those with symptomatic endogenous asthma.In normal subjects the 5-HT-uptake by platelets strictly obeyed Michaelis-Menten's kinetics. In patients with asymptomatic exogenous asthma, the active 5-HT-transport was moderately distorted in PRP and severely altered in PRP/PPP. Patients with sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
(8 reference statements)
1
12
0
1
Order By: Relevance
“…Although the significance of 5‐hydroxytryptamine in the pathophysiology of obstructive airway diseases remains to be elucidated, the elevated plasma level in asthmatic patients [13] and the release of 5‐hydroxytryptamine from platelets during allergic reactions [38] may have a role in facilitating bronchoconstriction in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the significance of 5‐hydroxytryptamine in the pathophysiology of obstructive airway diseases remains to be elucidated, the elevated plasma level in asthmatic patients [13] and the release of 5‐hydroxytryptamine from platelets during allergic reactions [38] may have a role in facilitating bronchoconstriction in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Others reported that platelets from asthmatic patients produced an increased ratio of lipoxygenase to cyclo-oxygenase products from excess exogenous radiolabelled arachidonate in comparison with non-atopic controls [10]. Reduced serotonin uptake by platelets from patients with exacerbations of asthma has been associated with increased serum and whole blood serotonin concentrations [11]. In stable asthma, platelet serotonin uptake was normal [12].…”
mentioning
confidence: 99%
“…However, these studies were con-ducted when IgE was still not discovered, and very few data concerning the relationship between IgE and platelets in atopic individuals are available. More recent reports have dealt with a defective serotonin transport (23) and a possible dysfunction of the second phase of platelet aggregation in asthmatics compared with controls, though with conflicting results (9,25,34,35). However, it seems that a dysfunction in aggregation exists that correlates with elevated serum IgE levels and the presence of specific IgE (19).…”
mentioning
confidence: 99%